Challenge of Exhibiting Archival Materials, Role of Conservator and Exhibiting Conditions in Archives of Yugoslavia (Atlanti, 2016)
This paper focuses on the complex issue of the exposure, preservation and maintenance of archival documents in the Archives of Yugoslavia. The attention is brought to all types of damage, whether caused by internal factors, which are the result of the nature of the material from which the document was created, whether caused by external factors that affect the degradation of the exhibited archival material. The risks of exposure to temperature, relative humidity, light, air pollution, dust, dirt, etc. The success of the exhibition depends on high quality cooperation between conservators, archivists and designers. When it comes to the role of conservators in the process of exposure, it is necessary for a conservator to be included in the exhibition activity, starting from the earliest stages of planning. Protection issues should not be overlooked in favor of other priorities, such as exhibit design. Moreover, it is not allowed to expose the original in poor condition with the aim of making showcase more attractive. Archival documents should be exhibited in appropriate glass cases, that are safe and made of inert materials. Today, a large number of modern design models, which meet conservation standards and have a high level of security protection from theft or any other attack on the document , are available on the market. When it comes to the presentation of the Archives of Yugoslavia, as well as in most of the archives in Serbia, the existing cabinets are old, difficult to operate and maintain, therefore they are not good enough when it comes to protection for the material that is exposed.
Keywords: archive; exhibition; document presentation; damaging conditions